PROFIL REMAJA PERKOTAAN DALAM NOVEL TEENLIT LOVE IN B MINOR KARYA ANINDITA - Yolanda, Novi; WS, Hasanuddin; Hayati, Yenni (Universitas Negeri Padang, 2018)
This study aims to: (1) describe the pleasures of the personality, (2) describe the prestige of recreation, (3) describe the pleasure of the group, and (4) describe juvenile delinquency in novel teenlit Love in B Minor by Anindita. The data of this research is the element of the novel teenlit Love in B Minor by Anindita. The source of this research data is novel teenlit Love in B Minor by Anindita. Data analysis technique is done through four stages, namely first, inventory. Second, identifying and classifying data through speech / action of characters and narrators abstracted as urban teen profile data covering personality fun, recreational prestige, group fun and juvenile delinquency. Third, interpret the data. Fourth draw conclusions and make a report. The results include 14 personality pleasure data, 8 recreational prestige data, 10 joy group data and 2 juvenile delinquency data in novel teenlit Love In B Minor by Anindita.Keywords : urban teenagers, teenlit novel, literature